BRAC's microfinance canvass: financial services and strategic linkages - Matin, Imran; Alam, Amiul (BRAC, 2019)
The poor are a diverse group with diverse livelihoods, needs and potential, which change over time due to lifecycle, new opportunities and external shocks. This diverse and dynamic reality of poor peoples' lives forms the canvass within which BRAC conceptualizes and designs its repertoire of development programs, in which microfinance is a core element. This paper through a few program experiences attempts to reveal the conceptual innovativeness embedded in the way BRAC thinks and acts about microfinance. It is not only 'microfinance the tool' that is a powerful poverty-alleviating weapon, but also the institutional framework of microfinance that is created in delivering microfinance. The extensive outreach, connection, knowledge and network, that the microfinance institution and the people running it at all levels possess and generate in their every day working engagements, is an extremely powerful asset in the fight to overcome poverty. We are only beginning to harness the power embodied in the institutional capital of microfinance institutions. This will be the second generation challenge for all poverty focused microfinance institutions and Bangladesh can again lead the way.